State’s Active Foreign Policy A Theoretical Study - Ahmed Babakr Ahmed (QALAAI ZANIST JOURNAL, 2020)
It is important to say that every country has a foreign policy, it is an important foundation of the state, and the state, for the sake of interest in this policy, occupies all strengths and capabilities to reach its goals in the foreign policy that serves domestic policy. Countries that correctly occupy their strengths and capabilities and put them at the service of their domestic policy will get good results. On the contrary, if all the power, ability and resources of the state were not put to use and were not utilized properly, it could not play an effective role in international politics. So, as far as the state realizes its power and ability, its strategy and its operation, it is close to reaching its foreign policy goals. Geopolitics, economics, military and technology, etc., have an important role to play in meeting the capabilities of state power. Nevertheless, nowadays, diplomacy plays an important role in creating relationships and creating opportunities and a suitable environment to reach the country's goals in international politics.